Multivariant process planning theory and its application for special purpose vehicle producing - Monka, Peter Pavol; Monková, Katarina (Advances in Mechanical and Materials Engineering)
The article deals with the characteristics of input and output data, which are necessary for manufacturing of machine parts of special purpose vehicles. It shows the relations between the individual manufacturing objects by means of information flow analysis within CAPP. It is possible to create several process plans for every engineering part and consequently use one of them in specific manufacturing conditions that are optimal according to the selected criterion. The analysis of information flow can considerably help with the process plan selection and, in result, with effectiveness or quality increasing.